2014
DOI: 10.1179/1743280414y.0000000048
|View full text |Cite
|
Sign up to set email alerts
|

Nanocomposite coatings: thermal spray processing, microstructure and performance

Abstract: The processing of nanomaterials and nanocomposites has advanced since the 1990s. The growth and opportunities afforded by this technological domain is evident through the trends of research and development (R&D) funding, Science Citation Index (SCI) publications, and patent applications presented in this paper. This article reviews the current state for the development of thermal sprayed nanocomposite coatings. The types of nanocomposite thermal spray feedstock materials that are available commercially, as wel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(29 citation statements)
references
References 358 publications
0
26
0
Order By: Relevance
“…One typical example is nanostructured WC-Co coatings. Though the CS of micro-sized WC-Co coatings showed poor deposition efficiency than that by HVOF, 244 the use of nanostructured feedstock significantly improves the deposition efficiency and density of CS coatings. This is possibly because the critical velocity is lowered and there is a higher surface area for contact between the binder phase and hard ceramic particles for effective deposition of nanostructured particles.…”
Section: Nanostructured Metal-ceramic Composite Coatingsmentioning
confidence: 95%
See 1 more Smart Citation
“…One typical example is nanostructured WC-Co coatings. Though the CS of micro-sized WC-Co coatings showed poor deposition efficiency than that by HVOF, 244 the use of nanostructured feedstock significantly improves the deposition efficiency and density of CS coatings. This is possibly because the critical velocity is lowered and there is a higher surface area for contact between the binder phase and hard ceramic particles for effective deposition of nanostructured particles.…”
Section: Nanostructured Metal-ceramic Composite Coatingsmentioning
confidence: 95%
“…The low porosity, absence of cracks, indistinguishable particle interfaces, and absence of spallation and delamination indicated that the CS nanostructured coatings may demonstrate good cohesion and adhesion. 244 Ajdelsztajn et al 144 nm. Elongated grains were also observed due to high velocity impact as shown in Figure 34b.…”
Section: Nanostructured Metallic Coatingsmentioning
confidence: 99%
“…There are areas of ultra-fine grain structure and nanostructure coexisting in the majority EPTed metals due to the rapid heating and cooling process. The future outlook demands such features as oriented texture to be dominant and manufactured in a controlled fashion rather than a curious and scientifically interesting anomaly [ 141 ]. The most appropriate pre-treatment before EPT is cold work, such as rolling and extrusion, since the effect of electric current pulses on recrystallization can be amplified in the pre-deformed materials [ 142 , 143 ].…”
Section: Challenges and Future Outlookmentioning
confidence: 99%
“…APS is the most usual and extensive method to prepare TBCs [10,11]. Research and development of nanotechnology and nanomaterials have further promoted and expanded the development of APS [12]. The plasma-sprayed nanostructured 8YSZ coatings can be obtained using nanostructured powder feedstocks and it has been demonstrated that nanostructured 8YSZ coatings present more remarkable properties than microstructured counterparts [13][14][15][16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%